2005
DOI: 10.1038/ncpgasthep0240
|View full text |Cite
|
Sign up to set email alerts
|

Current management of locally advanced pancreatic cancer

Abstract: Almost 30% of patients with pancreatic cancer present with large, locally advanced tumors in the absence of distant metastases. Because surgical resection is frequently contraindicated by vascular invasion, locally advanced pancreatic cancer has a dismal prognosis with a 6-10-month median survival. Recent advances in the multimodality treatment of other gastrointestinal malignancies have not altered the management of patients with locally advanced pancreatic cancer, a clinical dilemma reflected by the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
0
20
1
Order By: Relevance
“…Most patients with PDAC exhibit marked intrinsic resistance to radiation therapy and chemotherapy. Therefore, surgical resection is the only curative therapy but the disease is so aggressive that only 10% to 20% of patients qualify for surgery at the time of diagnosis (2). Therefore, identification of novel targets and development of new therapeutic approaches are urgently needed.…”
Section: Pancreatic Ductal Adenocarcinoma (Pdac) Is a Serious Healthmentioning
confidence: 99%
“…Most patients with PDAC exhibit marked intrinsic resistance to radiation therapy and chemotherapy. Therefore, surgical resection is the only curative therapy but the disease is so aggressive that only 10% to 20% of patients qualify for surgery at the time of diagnosis (2). Therefore, identification of novel targets and development of new therapeutic approaches are urgently needed.…”
Section: Pancreatic Ductal Adenocarcinoma (Pdac) Is a Serious Healthmentioning
confidence: 99%
“…Furthermore, at present, surgical resection offers the only chance for long-term survival for pancreatic cancer (4,5). However, the disease is so aggressive that only about 20% of patients are indication for surgery at the time of diagnosis (6). Therefore, identification of novel targets and development of new therapeutic approaches are required against pancreatic cancer to improve patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…
There is no consensus on the management of locally advanced pancreatic cancer, with either chemotherapy or combined modality approaches being employed (Maheshwari and Moser, 2005). No published meta-analysis (Fung et al, 2003;Banu et al, 2005;Liang, 2005;Bria et al, 2006;Milella et al, 2006) has included randomised controlled trials employing radiation therapy.
…”
mentioning
confidence: 99%
“…Ninety per cent of patients have unresectable disease at diagnosis, of whom 40 -50% have locally advanced disease (White et al, 1999), and reported to have better median survival of 6 -10 months compared to the 3 -6 months noted in metastatic disease (American Cancer Society, 2003). Radiotherapy approaches, with or without chemotherapy, have been frequently used in this subset (Maheshwari and Moser, 2005).…”
mentioning
confidence: 99%